Evaluation Of Investment Efficiency In Antam Gold, Sharia Stocks (Issi), And Foreign Currency (Usd) Based On Roi, Risk, And Maqāṣid Al-Sharīʿah - Depid Ismail (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2026)
This study aimed to evaluate the efficiency of three investment instruments obtained in Indonesia, specifically Antam gold, Sharia stocks (ISSI), and foreign exchange (USD) based on Return on Investment (ROI), risk (standard deviation), and their alignment with the principles of maqāṣid al-sharīʿah. A quantitative approach was employed using historical data from 2015 to 2024 sourced from official sources such as Logammulia.com, Investing.com, and Bank Indonesia. ROI and standard deviation were calculated using basic statistical formulas, while maqāṣid al-sharīʿah conformity was assessed through a scoring system involving ten indicators, including the protection of wealth, religion, life, intellect, progeny, and Islamic financial principles such as halal contracts, social justice, and contribution to the real economy. The findings revealed that Antam gold had the highest ROI and the best efficiency ratio with a very high maqāṣid score, positioning it as the most ideal investment instrument from an Islamic perspective. Sharia stocks scored with moderate efficiency, while USD investments showed the lowest efficiency and were the least aligned with maqāṣid al-sharīʿah. These findings indicated that investment efficiency in Islamic economics should encompass profitability, risk stability and blessings of sharia. This study contributes to the growing discourse on Islamic financial literacy by offering a holistic framework that integrates both financial performance and Sharīʿah compliance.